Effects of heat and humidity on cycling training and performance: A narrative review - Pardo Atarés, C.; Hueso Camañes, E.; Sitko, S. (Journal of Science and Cycling, 2023)
Heat and humidity are commonly listed as some of the most relevant environmental factors that may reduce cycling performance. Further, global warming may produce, in the upcoming years, a dramatic increase in heat stress during outdoor sporting events such as cycling. Accordingly, the interest in the assessment of the effects of heat stress has been recently accompanied by relevant scientific production regarding the true utility of training in hot and humid conditions for the optimization of performance both under thermoneutral and extreme environmental conditions. Current scientific evidence, as summarized in this narrative review, shows that cycling performance is severely impaired by heat and humidity. Specific heat training protocols and their effects are also reviewed to show their great potential to limit this impairment and also to potentially improve performance in thermoneutral environments.